8-5x+11+2x+4x-2=22

Simple and best practice solution for 8-5x+11+2x+4x-2=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-5x+11+2x+4x-2=22 equation:


Simplifying
8 + -5x + 11 + 2x + 4x + -2 = 22

Reorder the terms:
8 + 11 + -2 + -5x + 2x + 4x = 22

Combine like terms: 8 + 11 = 19
19 + -2 + -5x + 2x + 4x = 22

Combine like terms: 19 + -2 = 17
17 + -5x + 2x + 4x = 22

Combine like terms: -5x + 2x = -3x
17 + -3x + 4x = 22

Combine like terms: -3x + 4x = 1x
17 + 1x = 22

Solving
17 + 1x = 22

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + 1x = 22 + -17

Combine like terms: 17 + -17 = 0
0 + 1x = 22 + -17
1x = 22 + -17

Combine like terms: 22 + -17 = 5
1x = 5

Divide each side by '1'.
x = 5

Simplifying
x = 5

See similar equations:

| 6(t-5)+6t=4(3t+4)-11 | | 3.5(x+1.4y)+4(1.4x+1.3y)= | | 5+3s-2=8s+3-4s | | (3x+19/5)+(x+47/6)=17 | | (2/17)x=10 | | 3x-3.5=6.4x-16.42 | | 2t+7t=45 | | 7.79=2(3.14*r) | | (8-5i)(8-5i)= | | -(5y+5)-(-4y-6)=-3 | | 7.3x-8=6.3x+1 | | y/20=-26 | | 3(2x-1)+5=13 | | a=1/2(18*24) | | 1/6x=39 | | 17-3x=2x-2 | | 786=x+34+4(x-40) | | 8x5/9 | | -4(2b+3)+(9b-7)=0 | | 5(4x-6)-19x=7 | | 4x+1=2(x-7) | | b+8b-22=0 | | 3.5q-3.7-5.8q=-3.3q-3.9 | | 6y+5=5y-3 | | (21/25)(10/117)(27/14) | | 13-2/3x=3 | | 384-1/12 | | (8m-8m-27)(8m-25m-14)=0 | | .3(y)+.14(x)=.18 | | x+4x=58 | | -(3/5)x=(2/5) | | F(9)=100x-5 |

Equations solver categories